2018
DOI: 10.1016/j.brainres.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The P1 visual-evoked potential, red light, and transdiagnostic psychiatric symptoms

Abstract: A reduced P1 visual-evoked potential amplitude has been reported across several psychiatric disorders, including schizophrenia-spectrum, bipolar, and depressive disorders. In addition, a difference in P1 amplitude change to a red background compared to its opponent color, green, has been found in schizophrenia-spectrum samples. The current study examined whether specific psychiatric symptoms that related to these P1 abnormalities in earlier studies would be replicated when using a broad transdiagnostic sample.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Patients with MDD show increased FFC activity to sad faces and decreased activation to happy faces 82 , and slowed face emotion recognition 83 . Moreover, alterations in color processing are known both scientifically 53 , 84 87 and colloquially (“seeing the world through grey tinted glasses”) 88 in depression. More basic deficits in VIS function, such as alterations in sensory event-related potentials or center-surround inhibition of motion processing 89 are also reported, consistent with our VIS findings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MDD show increased FFC activity to sad faces and decreased activation to happy faces 82 , and slowed face emotion recognition 83 . Moreover, alterations in color processing are known both scientifically 53 , 84 87 and colloquially (“seeing the world through grey tinted glasses”) 88 in depression. More basic deficits in VIS function, such as alterations in sensory event-related potentials or center-surround inhibition of motion processing 89 are also reported, consistent with our VIS findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature on P1 in schizophrenics often the wave is computed by measuring individual peak amplitudes rather than using the mean amplitude within a time‐window around the peak. However, this methodological difference does not explain our results and their discrepancy from past studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a transdiagnostic approach focused on psychiatric symptoms, Bedwell and colleagues have carried out several studies on the visual P1 component. In their 2015 study, these authors found no differences in P1 amplitude among SCZ‐spectrum, chronic mood disorder, and non‐psychiatric control groups, whereas in their most recent work, they found a reduced bilateral P1 amplitude, with respect to HC, in SCZ but not in BD‐I patients . Impairments of early attentional mechanisms have also been observed in post‐traumatic stress disorder .…”
mentioning
confidence: 96%
“…Participants were provided a monetary stipend at the end of each session. The second session included EEG analysis of visual processing which has been published previously [14]; however, that publication did not include any data regarding cat interaction history.…”
Section: Participantsmentioning
confidence: 99%